Evaluación del desempeño laboral del personal de laboratorios Genfar S.A. y su incidencia en el clima organizacional, en el cantón Guayaquil, provincia del Guayas, período 2014. - Bastidas Álava, Lisseth Yajaira (2015)
The present research on performance appraisal GENFAR STAFF LABORATORIES SA AND ITS IMPACT ON THE ORGANIZATIONAL CLIMATE IN THE CANTON GUAYAQUIL, GUAYAS PROVINCE, 2014 PRESENTS PERIOD main objective, determine the performance assessment techniques that influence the organizational climate of workers, it is important to have a functional area the progress and improvement of the workers in the company. The theoretical foundation includes the following categories or studies: on the organizational climate, job performance, communication, workplace workers, technical evaluation of job performance, training in the area of human talent. Therefore the conceptual framework and the relevant legal framework, which mentions the Constitution of the Republic of Ecuador is made. The research results comprise the basis of surveys aimed to reviewers Genfar Laboratories SA Regarding the interview was the place to managers in the area of human talent and business unit, we were able to get necessary information about the job performance of workers for testing hypotheses namely "The job performance of the company staff Laboratory Genfar SA will affect the organizational climate in the Canton Guayaquil, Guayas province, 2014 period ".Among the results, we cite the most significant: In relation to the surveys of workers, it is shown with a percentage of 37% annual evaluations are conducted in addition the company uses assessment techniques work performance for their workers 65%, respectively. With respect to the discussion in which several authors expose their knowledge, theories and analysis, related material respects, contributing to the development of research they were compared. The conclusions were addressed, that part of the efficiency and effectiveness of their employees work depend on the evaluation techniques that make the area of human talent to extend the capabilities and skills, with a percentage of 74% assessments are essential to improve from work activities. The elaboration of the proposal on training for job performance of workers are essential for the progress and functioning of the company Laboratories SA Genfar For this reason the area of human talent should consider in its planning and organization as fundamental to measure the growth and improvement of its staff in the workplace part.It also recommends that the area of human talent, to focus on hiring people with work experience and profile according to the office or place to avoid various internal problems, the priority is the way to evaluate your personnel and improve its organizational climate.